Prediction model for the initial period, active period, and decline period of surface movement in coal mining - Liangliang ZHANG; Hua CHENG; Zhishu YAO; Xiaojian WANG (Meitan xuebao)
The duration of the initial, active, and declining periods of surface movement during coal mining is a key indicator for evaluating the stability of the surface, in response to the lack of theoretical prediction models for the duration of initial, active, and declining periods of surface movement in coal mining, based on the improved Knothe time model and the division of initial, active, and declining periods of surface movement, a theoretical prediction model for the duration of the initial period, active period, and declining period of surface movement is established, which only includes one model parameter and can comprehensively consider the influence of average mining depth, mining speed, coal mining height, loose layer thickness, bedrock layer thickness parameters. The rationality and accuracy of the theoretical prediction model were verified using monitoring data on the duration of surface movement in 15 mining faces. The results show that the prediction results of the initial period, active period, and declining period duration model of surface movement are basically consistent with the monitoring results of 15 mining areas, the minimum error is only 0 d, 1 d, and 0 d, and the average error is only 13.7 d, 12.7 d, and 18.5 d, respectively, verifying the rationality and accuracy of the prediction model. The initial period, active period, decline period, and entire surface movement duration all decrease nonlinearly with the increase of coal mining speed, and linearly increase with the increase of average mining depth, loose layer thickness and bedrock layer thickness However, the initial period and decline period of surface movement decrease nonlinearly with the increase of mining height, the active period and entire surface movement duration increase nonlinearly with the increase of mining height. The mining speed, average mining depth, mining height, loose layer thickness and bedrock layer thickness mainly affect the active period of surface movement and the entire surface movement duration, with little impact on the duration of the initial and declining periods. The research can provide certain reference for predicting the duration of surface movement in coal mining.